2016
DOI: 10.18438/b8x051
|View full text |Cite
|
Sign up to set email alerts
|

Parents of Young Children Select Picture Books Based on Information Not Found in Bibliographic Records

Abstract: the terms of the Creative Commons-AttributionNoncommercial-Share Alike License 4.0 International (http://creativecommons.org/licenses/by-nc-sa/4.0/), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly attributed, not used for commercial purposes, and, if transformed, the resulting work is redistributed under the same or similar license to this one. AbstractObjective -To determine how parents select picture books for their children, and which bib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…One research on picture books related to sustainable development just proposed a basic teaching outline and mentioned the triple bottom lines of sustainable development, i.e., ecology/environment, economy/jobs, and fair/equity, which was closer to real-world scenarios (Spearman & Eckhoff, 2012). Warren (2016) suggested that teachers and parents need a transparent and systemic framework for examining and selecting picture books. This especially applies to the sustainable development-oriented picture books that educators might not be familiar with.…”
Section: Discussionmentioning
confidence: 99%
“…One research on picture books related to sustainable development just proposed a basic teaching outline and mentioned the triple bottom lines of sustainable development, i.e., ecology/environment, economy/jobs, and fair/equity, which was closer to real-world scenarios (Spearman & Eckhoff, 2012). Warren (2016) suggested that teachers and parents need a transparent and systemic framework for examining and selecting picture books. This especially applies to the sustainable development-oriented picture books that educators might not be familiar with.…”
Section: Discussionmentioning
confidence: 99%
“…Improper organization of picture book information is not a problem faced just by children, however. Warren (2016) found that when parents selected picture books for children, existing library catalogs were inadequate. She suggested that catalogs need to provide more information about picture books, such as “cover images, sample pages, book condition, and information about the type of text.”…”
Section: Related Workmentioning
confidence: 99%